A novel transition clinic structure for adolescent and young adult patients with childhood onset rheumatic disease improves transition outcomes - Rebecca S. Overbury; Kelly Huynh; John Bohnsack; Tracy Frech; Aimee Hersh (BMC, 2021)
Background The transition of health care from Pediatric to Adult providers for adolescents and young adults with chronic disease is associated with poor outcomes. Despite the importance of this transition, over 80% of these patients do not receive the services necessary to transition to Adult health care. In 2018, we initiated a transition clinic structure, integrating an Internal Medicine - Pediatrics trained Adult Rheumatologist in a Pediatric Rheumatology clinic to guide this transition. Our goal was to improve transition outcomes. We report the methods of this clinic and its preliminary outcomes. Methods For patients referred to the transition clinic, the Adult Rheumatologist assumed medical management and implemented a six-part modular transition curriculum. This curriculum included a Transition Policy, Transition Readiness Assessment, medication review and education, diagnosis review and education, and counseling on differences between Pediatric and Adult-oriented care. Eligible patients and their families were enrolled in a prospective observational outcomes research registry. Initial data from this transition clinic is reported including adherence with certain aspects of the transition curriculum and clinic utilization. Results The transition clinic Adult Rheumatologist saw 177 patients in 2 years, and 57 patients were eligible for, approached, and successfully enrolled in the registry. From this registry, all patients reviewed the Transition Policy with the Adult Rheumatologist and 45 (78.9%) completed at least one Transition Readiness Assessment. Of the 22 patients for whom transition was indicated, all were successfully transitioned to an Adult Rheumatologist. 17 (77.3%) continued care post-transition with the transition clinic Adult Rheumatologist, and 5 (22.7%) continued care post-transition with a different Adult Rheumatologist. The median time between the last transition clinic visit and first Adult clinic visit was 5.1 months. Conclusions Our experience demonstrated the success of our clinic model regarding participation in the transition curriculum and improved clinic utilization data. Our results are an improvement over transition rates reported elsewhere that did not implement our model. We believe that this structure could be applied to other primary care and subspecialty clinics. Trial registration This research was approved by the University of Utah Institutional Review Board (IRB) in January 2019 (IRB_00115964). Patients were retrospectively registered if involved prior to this date.